Autoimmunity to specific citrullinated proteins gives the first clues to the etiology of rheumatoid arthritis. - Wegner, N; Lundberg, K; Kinloch, A; Fisher, B; Malmström, V; Feldmann, M; Venables, P (2010)
Rheumatoid arthritis (RA) is now clearly a true autoimmune disease with accumulating evidence of pathogenic disease-specific autoimmunity to citrullinated proteins. Citrullination, also termed deimination, is a modification of arginine side chains catalyzed by peptidylarginine deiminase (PAD) enzymes. This post-translational modification has the potential to alter the structure, antigenicity, and function of proteins. In RA, antibodies to cyclic citrullinated peptides are now well established for clinical diagnosis, though we argue that the identification of specific citrullinated antigens, as whole proteins, is necessary for exploring pathogenic mechanisms. Four citrullinated antigens, fibrinogen, vimentin, collagen type II, and alpha-enolase, are now well established, with others awaiting further characterization. All four proteins are expressed in the joint, and there is evidence that antibodies to citrullinated fibrinogen and collagen type II mediate inflammation by the formation of immune complexes, both in humans and animal models. Antibodies to citrullinated proteins are associated with HLA 'shared epitope' alleles, and autoimmunity to at least one antigenic sequence, the CEP-1 peptide from citrullinated alpha-enolase (KIHAcitEIFDScitGNPTVE), shows a specific association with HLA-DRB1*0401, *0404, 620W PTPN22, and smoking. Periodontitis, in which Porphyromonas gingivalis is a major pathogenic bacterium, has been linked to RA in epidemiological studies and also shares similar gene/environment associations. This is also the only bacterium identified that expresses endogenous citrullinated proteins and its own bacterial PAD enzyme, though the precise molecular mechanisms of bacterial citrullination have yet to be explored. Thus, both smoking and Porphyromonas gingivalis are attractive etiological agents for further investigation into the gene/environment/autoimmunity triad of RA.